Strength behind the mask: Supporting resilience in healthcare workers - Janitra, Fitria Endah; Nguyen, Trung (Palembang MediRose Publisher, 2024)
Healthcare professionals are integral to the effective operation of health systems. Despite their commitment, many experience persistent stress, burnout, and emotional exhaustion. Although resilience is frequently perceived as an individual characteristic, it is equally influenced by organizational support and workplace conditions. This editorial underscores the necessity of redefining resilience as a systemic responsibility. By fostering environments that cultivate resilience, healthcare systems not only safeguard their workforce but also improve patient outcomes and the overall efficacy of health systems.